MEASURING THE QUALITY OF DISTRICT GOVERNMENT WEBSITES ONLY USING THE MCCALL AND EUCS METHOD (END USER COMPUTING SATISFACTION) - Riswanto, Ando; Sari, Renny Puspita; Mutiah, Nurul (Universitas Royal, 2024)
Abstract: Technological developments are currently increasing rapidly, especially in the innovation of information data management. With so many media providing informationand services online, as well as the services provided by the Government of Sekadau Regency in the form of Webstie sekadaukab.go.id. Based on the survey results, the problems experienced by users are output and performance from sekadaukab.go.id still does not meet user expectations. Study this aims to measure the quality of information systems sekadaukab.go.id and also measure the level of user satisfaction with sekadaukab.go.id. By using the method McCall and EUCS (End User Computing Satisfaction) and using methods IPA (Importance Performance Analysis) to map variables into the level of importance and level of performance, the variables used are the variables in the method EUCS (End User Computing Satisfaction). Questionnaires were distributed to 100 users sekadaukab.go.id. The average quality generated by the method McCall of 43.6%, included in the pretty good category. For the results of measuring user satisfaction methods EUCS (End User Computing Satisfaction), each variable is included in the doubtful category range value 2.60 – 3.39. There are 18 recommendations for improvement based on the method McCall and the IPA method to the Kominfo Sekadau Regency against sekadaukab.go.id. Keywords: EUCS; IPA; McCall; public service; quality system Abstrak:Perkembangan teknologi saat ini semakin pesat, khususnya pada inovasi pengelolaan data informasi. Dengan banyaknya media menyediakan informasi dan pelayanan secara online, begitu juga dengan pelayanan yang disediakan oleh Pemerintah Kabupaten Sekadau berupa Webstie sekadaukab.go.id. Berdasarkan hasil survey, permasalahan yang dialami oleh pengguna yaitu output dan kinerja dari sekadaukab.go.id masih belum memenuhi harapan pengguna. Penelitian ini bertujuan untuk mengukur kualitas dari sistem informasi sekadaukab.go.id dan juga mengukur tingkat kepuasan pengguna terhadap sekadaukab.go.id. Dengan menggunakan metode McCall dan EUCS (End User Computing Satisfaction) serta menggunakan metode IPA (Importance Performance Analysis) untuk memetakan variabel kedalam tingkat kepentingan dan tingkat kinerja, variabel yang digunakan yaitu variabel pada metode EUCS (End User Computing Satisfaction). Kuesioner dibagikan kepada 100 orang pengguna sekadaukab.go.id. Rata- rata kualitas yang dihasilkan berdasarkan metode McCall sebesar 43,6%, masuk kedalamkategori cukup baik. Untuk hasil pengukuran kepuasan pengguna metode EUCS (End User Computing Satisfaction), masing-masing variabel masuk kedalam kategori ragu- ragu dengan range nilai 2.60 – 3.39. Terdapat 18 rekomendasi perbaikan berdasarkan pada metode McCall dan metode IPA kepada pihak Kominfo Kabupaten Sekadau terhadap sekadaukab.go.id. Kata kunci: EUCS; IPA; kualitas sistem; MCCALL; pelayanan publik